2014
DOI: 10.3844/ajabssp.2014.490.502
|View full text |Cite
|
Sign up to set email alerts
|

ELECTROLYSIS OF SWINE MANURE EFFLUENTS USING THREE DIFFERENT ELECTRODES Fe-Fe, Al-Al AND Fe-Al

Abstract: Swine effluent with high organic strength need to be treated to make it suitable for applying to crop/pasture fields, or discharging to any waterways. Electrocoagulation is a relatively simpler and cheaper technique over biological and chemical treatment methods currently used to treat high-strength industrial and municipal wastewater. The performance of an electrocoagulation system mainly depends on the pH, Electrical Conductivity (EC) of the medium, Chemical Oxygen Demand (COD) loading rates and catalytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In this research, aluminum based electrodes (Al-Al and Al-Fe) removed more TP and COD compared to Fe-Fe electrodes. This was likely due to excess active ionization when aluminum ion combined with the hydroxyl ion (OH-) and contributed to the generation of higher amounts of aluminum hydroxide (Al(OH) 3 ) (Hong et al, 2013;Lindsay et al, 1996;Rahman and Borhan, 2014). Elemental analysis of sludge revealed that except iron residue produced by the Fe-Fe electrodes and aluminum residue produced by Al-Al electrodes and both residue presented for hybrid electrode, rest of elemental residue presented in sludge was due to the sedimentation of metal residue in a sludge during an electrocoagulation process.…”
Section: Comparison Of Percentage Reduction Of Tp Tn and Cod During mentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, aluminum based electrodes (Al-Al and Al-Fe) removed more TP and COD compared to Fe-Fe electrodes. This was likely due to excess active ionization when aluminum ion combined with the hydroxyl ion (OH-) and contributed to the generation of higher amounts of aluminum hydroxide (Al(OH) 3 ) (Hong et al, 2013;Lindsay et al, 1996;Rahman and Borhan, 2014). Elemental analysis of sludge revealed that except iron residue produced by the Fe-Fe electrodes and aluminum residue produced by Al-Al electrodes and both residue presented for hybrid electrode, rest of elemental residue presented in sludge was due to the sedimentation of metal residue in a sludge during an electrocoagulation process.…”
Section: Comparison Of Percentage Reduction Of Tp Tn and Cod During mentioning
confidence: 99%
“…In the past, limited studies on the use of electrocoagulation were performed on livestock wastewater including swine (Bejan et al, 2007;Cho et al, 2010;Laridi et al, 2005;Rahman and Borhan, 2014), dairy (Bensadok et al, 2011;Şengil, 2006;Tchamango et al, 2010;Yavuz et al, 2011), slaughter house wastewater (Bazrafshan et al, 2012), industrial effluents (Ali and Yaakob, 2012;Basha et al, 2008), pharmaceutical wastewater (Yi-zhong et al, 2002), agroindustry and textile dye wastewater (Merzouk et al, 2009). However, until today, electrocoagulation was not use to treat feedlot runoff.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage removal of COD ( Hamada et al., 2018 ; Rahman and Borhan, 2014 ) was determined according to the following formula shown in Eq. (7) .…”
Section: Methodsmentioning
confidence: 99%
“…For example, dairy WW treatment was performed by the electro-Fenton's process [58]. ETCG was investigated for the treatment of agro-industry WW [59] and of swine manure effluents [60]. In addition, many studies have shown that ETCG can efficiently treat effluents containing metal ions, such as As, Ni, Cr, Cd +2 , B and steel slag.…”
Section: Wwelmentioning
confidence: 99%